Mechanisms of the impact of exercise intervention on college students' mental health: a longitudinal experimental study using swimming as an example - Wang, Wen; Yu, Linling; Huang, Le; Gao, Xing (Frontiers in Psychology, 2025)
IntroductionWith the growing prevalence of mental health issues among college students, there is a pressing need for effective and accessible intervention strategies. This study explores the potential of swimming as a structured intervention to improve students' emotional well-being, social adaptation, and academic stress management.MethodsA 15-week swimming intervention program was implemented among 44 college students, who were randomly assigned to either an experimental group (swimming intervention) or a control group (no intervention). Psychological assessments were conducted before and after the intervention to evaluate changes in emotional state, social functioning, and academic stress.ResultsStudents in the experimental group showed significant improvements in emotional stability (3.85 ± 0.78 vs. 3.52 ± 0.80, P = 0.01) and relaxation (3.82 ± 0.75 vs. 3.25 ± 0.61, P = 0.02). Positive changes were also observed in social adaptation, including interpersonal harmony (4.14 ± 0.73, P = 0.03) and perceived social support (4.21 ± 0.75, P = 0.04). Additionally, academic composure (3.57 ± 0.82 vs. 3.05 ± 0.83, P = 0.02) and goal management ability (3.73 ± 0.78, P = 0.04) significantly improved.DiscussionThe findings demonstrate that a structured swimming program can be an effective intervention for enhancing mental health among college students. It fosters emotional regulation, strengthens social ties, and improves coping strategies for academic stress. Further research is recommended to assess the long-term benefits and generalizability across broader populations.